Stiffness-dependent in vitro uptake and lysosomal acidification of colloidal particles - Hartmann, Raimo; Weidenbach, Marcel; Neubauer, Martin; Fery, Andreas; Parak, Wolfgang J. (Angewandte Chemie International Edition, 2015)
The physico-chemical properties of colloidal particles determine their uptake into cells. For a series of microparticles only one parameter, the mechanical stiffness, was varied, whereas other parameters such as size, shape, and charge were kept constant. The uptake was monitored in situ by analyzing individual particle trajectories including the progress of endocytosis, derived from local pH measurements around each particle. Evidence is presented that soft particles with low stiffness are transported faster to lysosomes than stiffer ones.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Biosensors; Mechanical properties; Nanoparticles; Polymeric capsules